1986
DOI: 10.1139/v86-377
|View full text |Cite
|
Sign up to set email alerts
|

Fast disproportionation of hexacyanomanganate(III) in acidic solution. Formation of hexacyanomanganate(IV) and kinetics of its decomposition

Abstract: GUILLERM~ L~PEZ-CUETO and CARLOS UBIDE. Can. J. Chem. 64, 2301 (1986).When potassium hexacyanomanganate(II1) dissolves in acidic solution it rapidly disproportionates into hexacyanomanganate(1V) and Mn(I1). Hexacyanomanganatc(1V) then slowly decomposes to yield Mn(I1) and (CN)2. Kinetics of the latter reaction has been studied. The reaction is found to be first order with respect to M~( c N~-, Hi, and Mn ( respectively. A mechanism with three parallel pathways is proposed, the deduced rate law being similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…That is consistent with the following stoichiometry The manganese(1V) produced will remain in the form of cyano complex (Fig. l), while manganese(I1) will form the aquo complex (10,11). Though the remaining acidic solution of the Mn(1V) cyano complex decomposes, this reaction proceeds very slowly at low temperature (1 1) and therefore only quite slow changes are observed in the voltammogram after the disproportionation reaction has gone to completion.…”
Section: Current-potential Curvessupporting
confidence: 82%
See 1 more Smart Citation
“…That is consistent with the following stoichiometry The manganese(1V) produced will remain in the form of cyano complex (Fig. l), while manganese(I1) will form the aquo complex (10,11). Though the remaining acidic solution of the Mn(1V) cyano complex decomposes, this reaction proceeds very slowly at low temperature (1 1) and therefore only quite slow changes are observed in the voltammogram after the disproportionation reaction has gone to completion.…”
Section: Current-potential Curvessupporting
confidence: 82%
“…is dissolved in acidic solution it rapidly disproportionates to yield ~n ( H 2 0 ) 6 ' + and (10,11) and this explains why a change in the uv-visible spectra of the fresh acidic solutions of M~( c N )~~-is observed. The manganese(1V) cyano complex formed decomposes to Mn(H20)6'+ and (CN)', but the reaction is auite slow at room temDerature (1 1) and thus ~, the M~( c N )~~-solution can be used for oxidizing purposes for a period of time (12).…”
mentioning
confidence: 99%
“…In acidic solution, however, [Mn(CN) 6 ] 3− undergoes disproportionation and decomposition reactions producing hexacyanomanganate(IV), [Mn(CN) 6 ] 2− , as shown in reactions (5) and (6) [38]. …”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the disproportionation reaction (5) was very fast and quantitative at room temperature [38] yielding [Mn(CN) 6 ] 2− ion. Although this complex is more stable in acidic medium, it was also found to slowly decompose producing Mn(II) (e.g., Mn(H 2 O) 6 2+ ) and cyanogen gas, (CN) 2 according to the reaction (6) [38].…”
Section: Resultsmentioning
confidence: 99%
“…radicals and complex species of Fez+ would be generated. Although this kind of rupture is unusual, a few references were found in the literature involving complexes of cobalt, chromium, and others (28)(29)(30)(31)(32)(33)(34); it was also found in the decomposition of hexacyanomanganate(II1) and hexacyanomanganato(1V) ions in aqueous acid media (35,36). However, the best proof was recently supplied (37): potassium ferricyanide is slowly reduced under dry air atmosphere, forming cyanogen and ferricyanide in small amounts, according to reactions [8] Rhodes' test (38) for the detection of cyanogen was negative,' which means that CN.…”
Section: 13mentioning
confidence: 93%